Tinospora cordifolia derived biomass functionalized ZnO particles for effective removal of lead(ii), iron(iii), phosphate and arsenic(iii) from water. Issue 59 (24th October 2019) - Vyas, Gaurav; Bhatt, Shreya; Paul, Parimal
Abstract : Owing to the vast diversity in functional groups and cost effectiveness, biomass can be used for various applications. Abstract : Owing to the vast diversity in functional groups and cost effectiveness, biomass can be used for various applications. In the present study, biomass from Tinospora cordifolia ( TnC ) was prepared and grafted onto the surface of ZnO particles following a simple method. The TnC functionalized ZnO particles (ZnO@ TnC ) were characterized and exhibited excellent adsorption properties towards Pb 2+ (506 mg g −1 ), Fe 3+ (358 mg g −1 ) and PO4 3− (1606 mg g −1 ) and the Fe 3+ adsorbed ZnO@ TnC adsorbs AsO2 1− (189 mg g −1 ); the metal ions and anions were analyzed by ICP and IC. For reuse of ZnO@ TnC, a desorption study was successfully carried out using NaOH and EDTA for PO4 3− and Pb 2+, respectively; Fe 3+ was further used for adsorption of As(iii ). The adsorption fits well with the Langmuir adsorption isotherm model and the adsorption kinetic data are best fitted with a pseudo-second-order equation. The system developed may be useful for treatment of waste water and industrial effluents.